Which is the top player for the cardiovascular safety? ibrutinib vs. obinutuzumab in CLL - Mascolo, Annamaria; Di Napoli, Raffaella; Balzano, Nunzia; D’Alessio, Elena; Izzo, Imma; Rossi, Francesco; Paolisso, Giuseppe; Capuano, Annalisa; Sportiello, Liberata (Frontiers in Pharmacology, 2023)
Introduction: Ibrutinib, a Bruton’s tyrosine kinase (BTK) inhibitor, is authorized for the treatment of chronic lymphocytic leukemia (CLL). This study aims to explore the cardiac safety profile of ibrutinib in comparison with obinutuzumab. Methods: A retrospective pharmacovigilance study was conducted on data retrieved from the European pharmacovigilance database (Eudravigilance) from 1 January 2014 to 30 September 2022. To compare the reporting frequency of cardiovascular events among ibrutinib, obinutuzumab, and the combination of both. Results: A total of 2 291 CV cases were retrieved, of which 1965 were related to ibrutinib, 312 to obinutuzumab, and 14 to the combination. Most cases referred to patients aged ≥65 years (N = 1,454; 63.47%) and male (N = 1,497; 65.34%). Most cases were serious (N = 2,131; 93.02%). The most reported events were: atrial fibrillation (N = 913; 31.31%) and haemorrhage (N = 201; 6.89%). A higher reporting frequency of CV events was found when ibrutinib was compared to obinutuzumab (ROR, 3.22; 95% CI, 2.89-3.60) or combination (ROR, 1.77; 95% CI, 1.11-2.83). A lower reporting was observed when obinutuzumab was compared to combination (ROR, 0.55; 95% CI, 0.34-0.88). Discussion: A higher reporting frequency of CV events in patients exposed to ibrutinib in comparison with obinutuzumab was found. Further studies are needed to better explore the safety of ibrutinib.